1991
DOI: 10.1093/clinchem/37.10.1683
|View full text |Cite
|
Sign up to set email alerts
|

Determination of silver in blood, urine, and tissues of volunteers and burn patients

Abstract: Silver sulfadiazine cream (SSD) has been used successfully in the management of burn wound sepsis. Silver deposition has been found in the skin, gingiva, cornea, liver, and kidney of patients treated with this cream, causing argyria, ocular injury, leukopenia, and toxicity in kidney, liver, and neurologic tissues. Monitoring concentrations of silver in blood and urine of patients receiving this treatment has become necessary, but sensitive and suitable methods adaptable to a clinical laboratory are still neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(106 citation statements)
references
References 0 publications
3
103
0
Order By: Relevance
“…In one patient, a postmortem examination after the use of SSD revealed elevated silver levels in the liver, kidney, and cornea. 19 Another patient with 30% BSA burn reported by Iwasaki et al had markedly elevated silver levels in the brain (617.3 ng/g wet weight) after application of SSD and end-stage kidney disease. 24 We did not investigate SSD as wound treatment in our study because the pharmaceutical form of SSD as a 1% cream for external use needed daily dressing changes that could not be provided by our study group long term over 6 weeks.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In one patient, a postmortem examination after the use of SSD revealed elevated silver levels in the liver, kidney, and cornea. 19 Another patient with 30% BSA burn reported by Iwasaki et al had markedly elevated silver levels in the brain (617.3 ng/g wet weight) after application of SSD and end-stage kidney disease. 24 We did not investigate SSD as wound treatment in our study because the pharmaceutical form of SSD as a 1% cream for external use needed daily dressing changes that could not be provided by our study group long term over 6 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…18 Various reports describe the uptake of externally applied silver, mainly silver sulfadiazine (SSD), into the blood in burn patients. 19,20 However, studies on silver levels of different organs and tissues after external application of silvercontaining wound dressings after major burns are scarce. A recent study from Brandt et al reports elevated silver levels in different organs, blood, and feces in hairless mice, externally treated with different silver formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Such absorption may lead to hypersensitivity reactions, such as neutropenia and erythema multiforme (Lockhart et al, 1983). Wan et al (1991) determined that urinary excretion of silver and silver concentrations in plasma increased with the application of a standard solution of silver containing AgNO 3 . Balogh et al (1985) found in an in vivo study that the application of povidone-iodine resulted in higher iodine levels in the plasma and higher iodine excretion in the urine of burn patients than traumatized patients.…”
Section: Heating Brandingmentioning
confidence: 99%
“…The multivariate analysis showed that anaemia was a risk factor for increased serum silver at D28 (OR = 5.33 [1. [14][15][16][17][18][19][20][21][22][23][24].90] P = 0.033) and that a higher albumin serum was protective for increased serum silver at D28 (OR = 0.844 [0.73-0.98] P = 0.029). Indeed, each increase in the sera albumin dosage of 1 g/L diminished the risk of increased serum silver.…”
Section: Resultsmentioning
confidence: 99%
“…The dressings involved in these studies were SSD and Acticoat TM . [18][19][20][21][22] Moreover, Karlmarsk et al's study showed that silver absorption tended to be higher in patients with larger venous ulcers. 15 In our study, the highest observed silver level was 14.2 lg/L, which is much higher than detected in previous studies (<8.6 lg/L).…”
Section: Discussionmentioning
confidence: 99%